Behavioral Auditory Processing in Children and Young Adults with Autism Spectrum Disorder. - Schafer, Erin C.; Mathews, Lauren; Gopal, Kamakshi; Canale, Emilee; Creech, Avery; Manning, Jacy; Kaiser, Kara (Journal of the American Academy of Audiology, 2020)
Background Auditory-processing deficits are common in children and adults who are diagnosed with autismspectrum disorder (ASD). These deficits are evident across multiple domains as exhibited by the results from subjective questionnaires fromparents, teachers, and individuals with ASD and from behavioral auditory-processing testing. Purpose Few studies compare subjective and behavioral performance of adults and children diagnosed with ASD using commercially available tests of auditory processing. The primary goal of the present study is to compare the performance of adults and children with ASD to age-matched, neurotypical peers. The secondary goal is to examine the effect of age on auditory-processing performance in individualswith ASD relative to age-matched peers. Research Design A four-group, quasi-experimental design with repeated measures was used in this study. Study Sample Forty-two adults and children were separated into four groups of participants: (1) 10 children with ASD ages 14 years or younger; (2) 10 age-matched, neurotypical children; (3) 11 adolescents and young adults with ASD ages 16 years and older; and (4) 11 age-matched, neurotypical adolescents or young adults. Data Collection and Analysis Data from each participant were collected in one test session.Data were analyzed with analysis of variance (ANOVA), repeatedmeasuresANOVA, or nonparametric analyses. Effect sizes were calculated to compare performance between those with ASD and those who were neurotypical within each age group. Results Across all the questionnaires and the majority of the behavioral test measures, participants with ASD had significantly poorer ratings or auditory-processing performance than age-matched, neurotypical peers. Adults had more favorable performance than children on several of the testmeasures. Medium to large effect sizes corroborated the significant results. Conclusion Overall, the questionnaires and behavioral tests used in this study were sensitive to detecting auditory-processing differences between individuals diagnosed with ASD and those who are considered neurotypical. On most test measures, children performed more poorly than adults. The findings in this study support that both children and adults with ASD exhibit auditory-processing difficulties. Appropriate school and work accommodations will be necessary to ensure appropriate access to speech in challenging environments.